Peran Guru Taman Pendidikan Al-Qur'an Surau Balenggek Sikabu Bukit Lubuk Alung dalam Membentuk Kedisiplinan Ibadah Shalat Anak - Merheliza Syirly; Wirdati Wirdati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to determine the role of the teacher as a motivator and a mentor in shaping the discipline of children's prayer at the Al-Qur'an Education Park at Surau Balenggek Sikabu Bukit, Lubuk Alung. (1) Background: The implementation of prayer discipline education at the Al-Qur'an Education Park (TPA) is not going well. Due to the lack of motivation from within the students and the lack of awareness from within themselves of their obligations as Muslims to establish/perform the five daily prayers a day and night; (2) Methods: This research uses qualitative research with a case study approach. With samples of TPA teachers in the field of worship and morals, and TPA teachers in the field of Al-Qur'an Arts. The research instruments in this study were interview guides, recording devices, writing instruments, and other supporting tools that support the research process; (3) Results: The teacher's role as a motivator in shaping the discipline of santri prayer is to provide support and encouragement, provide assessments, and give awards. While the teacher's role as a mentor is to provide guidance, reprimand and punishment, advice and ibrah/i'tibar. In addition, the teacher's role as a motivator and mentor also applies learning methods, such as exemplary methods, habituation, awareness, and supervision; (4) Conclusion: The teacher's role as a motivator: providing support and encouragement, assessment, and appreciation. The teacher's role as a mentor: providing guidance, reprimand and punishment, advice, ibrah/i'tibar, applying exemplary methods, habituation, awareness, and supervision.